Stable coronary heart disease treatment: focus on beta-adrenoblockers - V. I. Makolkin (Кардиоваскулярная терапия и профилактика)
Stable angina treatment with a prolonged-action beta-adrenoblocker, metoprolol succinate, is discussed. Themedication is effective, metabolically neutral, well tolerated and could also be used in patients with comorbidities.